My reminiscences - Tagore, Rabindranath (Rupa & Co, 2008)
My Reminiscences (1917), translated by Surendranath Tagore (Jibansmriti, 1912), is an autobiographical account of the first twenty-seven formative years of Tagore's life.-- preuzeto s korica.